Efficacy of Intravenous Lidocaine During Endoscopic Submucosal Dissection for Gastric Neoplasm: A Randomized, Double-Blind, Controlled Study. Issue 18 (May 2016) - Kim, Ji Eun; Choi, Jong Bum; Koo, Bon-Nyeo; Jeong, Hae Won; Lee, Byung Ho; Kim, So Yeon
Abstract : Abstract: Endoscopic submucosal dissection (ESD) is an advanced therapy for early gastric neoplasm and requires sedation with adequate analgesia. Lidocaine is a short-acting local anesthetic, and intravenous lidocaine has been shown to have analgesic efficacy in surgical settings. The aim of this study was to assess the effects of intravenous lidocaine on analgesic and sedative requirements for ESD and pain after ESD. Sixty-six patients scheduled for ESD randomly received either intravenous lidocaine as a bolus of 1.5 mg/kg before sedation, followed by continuous infusion at a rate of 2 mg/kg/h during sedation (lidocaine group; n = 33) or the same bolus and infusion volumes of normal saline (control group; n = 33). Sedation was achieved with propofol and fentanyl. The primary outcome was fentanyl requirement during ESD. We recorded hemodynamics and any events during ESD and evaluated post-ESD epigastric and throat pain. Fentanyl requirement during ESD reduced by 24% in the lidocaine group compared with the control group (105 ± 28 vs. 138 ± 37 μg, mean ± SD; P  < 0.001). The lidocaine group reached sedation faster [40 (20–100) vs. 55 (30–120) s, median (range); P  = 0.001], and incidence of patient movement during ESD decreased in the lidocaine group (3% vs. 26%, P  = 0.026). Numerical rating scale for epigastric pain was significantly lower at 6 hours after ESD [2 (0–6) vs. 3 (0–8), median (range); P  = 0.023] and incidence of throat pain was significantly lower in the lidocaine group (27% vs. 65%, P  = 0.003). No adverse events associated with lidocaine were discovered. Administration of intravenous lidocaine reduced fentanyl requirement and decreased patient movement during ESD. Moreover, it alleviated epigastric and throat pain after ESD. Thus, we conclude that the use of intravenous adjuvant lidocaine is a new and safe sedative method during ESD.